Doxorubicin Induces Lamellipodia Formation and Cell Migration - Nur Dina Amalina; Ika Putri Nurhayati; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2017)
Breast cancer is the main cause of cancer death among women, especially breast cancer metastasis. Metastasis process begins with the ability of cell cancer invasion. Doxorubicin, a antracycline chemotheraphy, is known to induce TGFβ1, thus promote invasion. The aim of this study is to optimize doxorubicin doses to induce lamellipodia formation in 4T1 and MCF-7/HER2 cells. Lamellipodia formation was observed by morphological changes using microscope inverted. The effect of doxorubicin on cell viability was analyzed using MTT assay. Rac1 expression after doxorubicin exposure was determined by western blotting. Lamellipodia formation was observed by morphological change of the cell at the dose 10, 25, 50 and 100 nM. Doxorubicin at the dose of 10 nM could induced lamellipodia formation without affect cell viability in both 4T1 and MCF-7/HER2 cells.  Doxorubicin induced cell cycle arrest at G2/M phase at all doses. Doxorubicin 10 nM also decrease Rac1 expression compared to control.Key words: Doxorubicin, lamellipodia, Rac1, migration.